Metode Darb al-Amthâl dalam Penafsiran Muhammad ‘Abduh - Salim, Agus (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2015)
Muhammad ‘Abduh had ground the orientation of the Koran in the line of Muslim life. In other words, interpretations are always aiming to make the Koran as well as applying the guidance in public life as a solution to the problem of street life. Therefore, associated with verses mubham and mutashâbih, ‘Abduh closer to the bow of the salaf scholars who prefer silence and surrender fully to God’s intention (tafwîd). However, on several occasions, he sometimes shifts from the bow, for example, when in contact with mutashâbih verses, verses related to the supernatural, and the stories in the Koran as may be necessary to explain in detail. In this position, he sometimes refers to methods tamthîl as tafwîd form or otherwise as a form of ta’wîl. This article will explore the darb al-amthâl in view of ‘Abduh as one method of interpreting the Koran from his works that contain related ideas and his interpretation of the Koran and the consideration of the methods of darb al-amthâl